The Effect of patient position on Recording the Centric Relation of Occlusion by Tracing the Gothic Arch in Dentulous patients - F Rostamkhan; J Gharehchahi; H Akhavizadegan; N Asadzadeh Aghdaee; S Nosouhian (Isfahan University of Medical Sciences, 2008)
Introduction: Centric Relation (CR) is the most important recording procedure of maxillamandibularrelation in prosthodontic. We investigated the influence of patient's body position inCR recording by extra-oral tracing method.Materials and Methods: In this analytic cross-sectional study, 18 dentulous subjects were selectedrandomly. After patient education, the extra-oral tracing device attached to acrylic stents; Then theGothic arch tracing was accomplished in supine, semisupine and upright positions. The CRachieved by bimanual manipulation method was also recorded. Four points were recorded in fourtransparent sheets; also, the vertical (Y) and horizontal (X) axis were measured for each point.Then the horizontal, anterior- posterior and straight distances of each point to point that achievedby bimanual manipulation were calculated. Data were analyzed using the one-way ANOVA and ttestwith the significant level of I = 0.05.Results: There was no significant difference between horizontal distances of points registered invarious body positions and of point registered in Dawson method, but with a view to ant-post anddirect distance, the point registered in supine and semisupine positions were significantly nearer toDawson manner, rather than the points registered in upright position. No correlation to sex andage was obtained between distances of registered points in various body positions and registeredpoint in Dawson method.Conclusion: In dentulous subjects, in comparison to upright position, the obtained CR in supineand semi-supine positions by extraoral tracing method had significant similarity to bimanualmanipulation.Key words: Supine position, dental occlusion, tracing, dentulous